1998
DOI: 10.1099/0022-1317-79-12-3101
|View full text |Cite
|
Sign up to set email alerts
|

Ten distinct circular ssDNA components, four of which encode putative replication-associated proteins, are associated with the faba bean necrotic yellows virus genome.

Abstract: Four further circular ssDNA components (C7-C10), about 1 kb in size and structurally similar to the previously described components (C1-C6) found associated with a Syrian (Sy) isolate of faba bean necrotic yellows virus (FBNYV), have been identified. Similar to C1 and C2, two of the new components (C7 and C9) encode putative replicationassociated (Rep) proteins of 33n2 and 32n7 kDa, respectively, the former of which is 90 % identical to the C10 Rep protein of milk vetch dwarf virus (MDV). C8 encodes a putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…DNA 5 has been shown to contain an LXCXE motif, and binding between DNA 5 products and retinoblastoma (Rb), demonstrated by yeast two-hybrid analysis, may be involved in host-cell cycle manipulation (82). In addition, more than one Rep-encoded component may be associated with virus infection in nanoviruses (22,29,30,39,63). Only one of these Rep genes, master Rep, can directly replicate non-self-replicable components, and remaining Rep-encoded components are considered to be satellite viruses (29,78,80).…”
mentioning
confidence: 99%
“…DNA 5 has been shown to contain an LXCXE motif, and binding between DNA 5 products and retinoblastoma (Rb), demonstrated by yeast two-hybrid analysis, may be involved in host-cell cycle manipulation (82). In addition, more than one Rep-encoded component may be associated with virus infection in nanoviruses (22,29,30,39,63). Only one of these Rep genes, master Rep, can directly replicate non-self-replicable components, and remaining Rep-encoded components are considered to be satellite viruses (29,78,80).…”
mentioning
confidence: 99%
“…1), composed of iteron-like sequences flanking the IR sequences at the origin of replication with the potential of forming a stem-loop structure (8,31,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…No nanovirus component has been identified that contains an ORF similar to the internal ORF encoded by BBTV DNA-R. No function has been assigned to the ORFs located on the other nanovirus-specific components (DNA-U1 and DNA-U2). Multiple satellite DNAs, encoding non-essential Reps (otherwise known as para-Reps) have also been identified associated with nanoviruses, some of which shares homology with the satellite Rep encoding components of BBTV (Katul et al, 1995;Katul et al, 1998;Sano et al, 1998). …”
Section: Genus Nanovirusmentioning
confidence: 99%